Replication of H9 influenza viruses in the human ex vivo respiratory tract, and the influence of neuraminidase on virus release - Renee W. Y. Chan (Nature Portfolio, 2017)
Abstract H9N2 viruses are the most widespread influenza viruses in poultry in Asia. We evaluated the infection and tropism of human and avian H9 influenza virus in the human respiratory tract using ex vivo respiratory organ culture. H9 viruses infected the upper and lower respiratory tract and the majority of H9 viruses had a decreased ability to release virus from the bronchus rather than the lung. This may be attributed to a weak neuraminidase (NA) cleavage of carbon-6-linked sialic acid (Sia) rather than carbon-3-linked Sia. The modified cleavage of N-acetlylneuraminic acid (Neu5Ac) and N-glycolylneuraminic acid (Neu5Gc) by NA in H9 virus replication was observed by reverse genetics, and recombinant H9N2 viruses with amino acids (38KQ) deleted in the NA stalk, and changing the amino acid at position 431 from Proline-to-Lysine. Using recombinant H9 viruses previously evaluated in the ferret, we found that viruses which replicated well in the ferret did not replicate to the same extent in the human ex vivo cultures. The existing risk assessment models for H9N2 viruses in ferrets may not always have a strong correlation with the replication in the human upper respiratory tract. The inclusion of the human ex vivo cultures would further strengthen the future risk-assessment strategies.